Exploring P-Hailers' perceptions of job demand, control and social support regarding risk factor of musculoskeletal disorder - Nor Hidayah, Mohammad Isa (2024)
Musculoskeletal disorders (MSDs) are a widespread concern among workers, causing pain, mobility limitations, and functional impairments in muscles, joints, tendons, ligaments, nerves, and bones. Occupational groups like motorcyclists and P-hailing riders face elevated Musculoskeletal disorder (MSD) risks due to factors such as prolonged awkward postures, repetitive task, static and sustained motion, vibration exposure, and environmental factor. Hence, this study aims to explore the impact of job demand, job control, and social support on Musculoskeletal disorder (MSDs) risk factor among P-Hailer riders in Malaysia. This qualitative study has conducted semistructured in-depth interviews using open-ended questions as the main instrument to collect richer and descriptive data of each respondent's experiences. Purposive sampling is employed to select 10 food delivery riders based on specific criteria. Furthermore, this study has adopted an inductive approach to thematic analysis to draw better interpretation on the collected data. Subsequently Job Demand-Control-Support (JDCS) model is employed as the theoretical framework for this study to explain the findings. The study underscores the intricate interplay between job demands, job control, and social support in shaping the risk of musculoskeletal disorders among food delivery riders. While the physical demands of the job and time pressures contribute to MSDs, the flexibility in work arrangements and supportive networks help mitigate these risks. Last but not least, limitations and recommendations for future studies is drawn for the sake of future works in general